2019
DOI: 10.1021/acs.jafc.9b01069
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of DPP-IV-Inhibitory Peptides from Hydrolyzed-Rapeseed-Protein-Derived Napin with Analysis of the Interactions between Key Residues and Protein Domains

Abstract: Previously reported peptides derived from napin of rapeseed (Brassica napus) have been shown to inhibit DPP-IV in silico. In the present study, napin extracted from rapeseed was hydrolyzed by commercial enzymes and filtered by an ultrafiltration membrane. The napin hydrolysate was then purified by a Sephadex G-15 gel-filtration column and preparative RP-HPLC. A two-enzyme-combination approach with alcalase and trypsin was the most favorable in terms of the DPP-IVinhibitory activity (IC 50 = 0.68 mg/mL) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 49 publications
6
66
0
Order By: Relevance
“…Napin migrated as a doublet in the range of 5-10 kDa, whereas cruciferin migrated as double triplets, the upper one with protein bands in the range of 25-35 kDa and the lower one with bands in the range of 15-20 kDa (Figure 1). The protein electrophoretic profile matches those from earlier reports (Höglund et al, 1992;Wanasundara, 2011;Stone et al, 2014;Akbari and Wu, 2015;Perera et al, 2016;Joehnke et al, 2019;Xu et al, 2019;Rahman et al, 2020) ( Supplementary Figure 2A).…”
Section: Protein Characterizationsupporting
confidence: 86%
“…Napin migrated as a doublet in the range of 5-10 kDa, whereas cruciferin migrated as double triplets, the upper one with protein bands in the range of 25-35 kDa and the lower one with bands in the range of 15-20 kDa (Figure 1). The protein electrophoretic profile matches those from earlier reports (Höglund et al, 1992;Wanasundara, 2011;Stone et al, 2014;Akbari and Wu, 2015;Perera et al, 2016;Joehnke et al, 2019;Xu et al, 2019;Rahman et al, 2020) ( Supplementary Figure 2A).…”
Section: Protein Characterizationsupporting
confidence: 86%
“…In our previous study (Xu et al, 2019), the octapeptide ELHQEEPL (IC 50 = 78.46 ± 4.94 μM) was confirmed to demonstrate an excellent DPP-IV inhibitory DPP-IV using in vitro enzymatic assay.…”
Section: Introductionmentioning
confidence: 75%
“…The main objective of the study was to assess whether ELHQEEPL could maintain the same DPP-IV inhibitory activity in Caco-2 cell monolayers model as demonstrated in our previous results (Xu et al, 2019). Well-differentiated Caco-2 cells possess a microvilli structure on the apical surface, with potential polarity related to the basolateral side (Marques et al, 2011;Pshezhetsky et al, 2007), and have been reported to contain many brush border proteases (BBPs),…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Adding two more amino acids at the C terminus changes the DPP-IV inhibitory action and the modification of targeting regions and binding sites on DPP-IV. Until now, most food protein-derived peptides were reported to be noncompetitive inhibitors or uncompetitive inhibitors [ 19 , 34 , 39 , 40 , 41 ]. Therefore, this research recommends an innovative concept for developing DPP-IV inhibitory peptides for functional food industry.…”
Section: Resultsmentioning
confidence: 99%